The scientific literature on bats (chiroptera) in Brazil: a scientometric analysis from 1954 – 2018 - LUCIANO,BEATRIZ FERNANDES L. (2022)
Abstract Globally, bats are of interest in many studies, beyond their ecological or epidemiological relevance or even the ecomorphological diversity of species. In Brazil, most of the indexed studies on chiropterans date from 1954, with a slow and heterogeneous progress in the publication increasing. The aim of this study was to analyze the literature on bats in Brazil, identifying patterns, tendencies and knowledge gaps in the Brazilian federal states. We carried out a sistematyzed search on the online databases Clarivate Analytics Web of Science (WoS), Scientific Electronic Library Online (SciELO), PubMed and Scopus. We used the descriptive terms “Chiroptera” and “Brazil”. Besides these bases, we included data from the manuscripts published in Chiroptera Neotropical. We obtained a total of 1,115 articles, which were analyzed and classified in 22 thematic categories based on the articles’ approach. We observed that each Brazilian region and state had particularities in their knowledge panoramas of bats, not being possible to generalize conditions for each federal region. Even though the increasing in the number of articles by categories, we encourage that every approach keep being developded, once no thematic could had been considered enough explored till the moment.